2008
DOI: 10.1016/j.neuroimage.2007.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal P300 in people with high risk of developing psychosis

Abstract: Background: Individuals with an "At Risk Mental State" (or "prodromal" symptoms) have a 20-40% chance of developing psychosis; however it is difficult to predict which of them will become ill on the basis of their clinical symptoms alone. We examined whether neurophysiological markers could help to identify those who are particularly vulnerable.Method: 35 cases meeting PACE criteria for the At Risk Mental State (ARMS) and 57 controls performed an auditory oddball task whilst their electroencephalogram was reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 92 publications
7
62
1
Order By: Relevance
“…[44][45][46] In support of these findings, previous diffusion tensor imaging (DTI) studies in patients with schizophrenia have confirmed reduced anisotropy in the frontal cortex, 47-50 the anterior cingulum 51,52 and the tempor al lobe. 20,53 The ARMS group also showed a reduced P300 amplitude compared with controls, in line with our previous results in a larger sample 14 and with other studies in patients at risk for psychosis. 15,54 Functionally, the P300 reflects the summation of multiple, simultaneously occurring cognitive and brain processes that are linked to attentional resource allocation and memory-updating operations in the brain.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[44][45][46] In support of these findings, previous diffusion tensor imaging (DTI) studies in patients with schizophrenia have confirmed reduced anisotropy in the frontal cortex, 47-50 the anterior cingulum 51,52 and the tempor al lobe. 20,53 The ARMS group also showed a reduced P300 amplitude compared with controls, in line with our previous results in a larger sample 14 and with other studies in patients at risk for psychosis. 15,54 Functionally, the P300 reflects the summation of multiple, simultaneously occurring cognitive and brain processes that are linked to attentional resource allocation and memory-updating operations in the brain.…”
Section: Discussionsupporting
confidence: 91%
“…12 Interestingly, 3 recent independent studies of individuals at enhanced risk for psychosis have confirmed that P300 ab normalities are already evident in the prepsychotic phases. [13][14][15] P300 can index a neuro biologic vulnerability to schizophrenia, in line with other studies showing P300 abnormalities in relatives of individuals with psychosis. 16,17 On the other hand, neuroimaging studies have indicated that patients at high risk for psychosis show alterations in white matter 18,19 volume in fronto-temporal regions.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…[26][27][28] Several papers showed a reduced P300 amplitude in CHR subjects. [29][30][31][32][33][34] Yet, none of these reports included (enough) converted cases to enable a predictor analysis except for the DUPS study. 25 While all factors mentioned above contribute to the prediction of a first psychosis, their relative contribution is small.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis originates from the observation that negative symptoms and quantitative EEG (qEEG) spectral power are correlated in different types of medicated and unmedicated schizophrenic patients. [19][20][21][22][23][24][25][26][27] Moreover, a recent study by our group 28 showed that negative symptoms are positively correlated with qEEG absolute power in delta (0.5-4 Hz), theta (4-8 Hz) and beta1 (12)(13)(14)(15) bands in the first episode (FE) of schizophrenia in neuroleptic-naïve patients. Presence of these correlations in neuroleptic naïve FE patients is a first requirement for the combination of negative symptoms with qEEG findings in ARMS patients to be a valid predictor for transition to psychosis.…”
Section: Introductionmentioning
confidence: 99%